2018
DOI: 10.1039/c7cp07073j
|View full text |Cite
|
Sign up to set email alerts
|

Computational engineering of cellulase Cel9A-68 functional motions through mutations in its linker region

Abstract: Microbial cellulosic degradation by cellulases has become a complementary approach for biofuel production. However, its efficiency is hindered by the recalcitrance of cellulose fibres. In this context, computational protein design methods may offer an efficient way to obtain variants with improved enzymatic activity. Cel9A-68 is a cellulase from Thermobifida fusca that is still active at high temperatures. In a previous work, we described a collective bending motion, which governs the overall cellulase dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Computer-aided enzyme simulation enabled to redesign of Cel9A-68 cellulase from Thermobifida fusca with improved cellulase activity. Such features could be extremely relevant for cellulose degradation in the brewery sector [ 26 ]. A lipase from P. aeruginosa PAO1 was recently computationally “reverse-engineered” using proline mutations.…”
Section: Strategies and Challenges For The Development Of Engineered ...mentioning
confidence: 99%
“…Computer-aided enzyme simulation enabled to redesign of Cel9A-68 cellulase from Thermobifida fusca with improved cellulase activity. Such features could be extremely relevant for cellulose degradation in the brewery sector [ 26 ]. A lipase from P. aeruginosa PAO1 was recently computationally “reverse-engineered” using proline mutations.…”
Section: Strategies and Challenges For The Development Of Engineered ...mentioning
confidence: 99%
“…The presence of more flexible linkers resulted in higher cellulolytic activity. Thus, the linker mutations may prove to be an efficient way to improve enzyme activity (Costa et al, 2018).…”
Section: Computational Approachmentioning
confidence: 99%
“…Based on the previous study, Costa, Silva & Batista (2018) identified two residues (Gly460 and Pro461) located at the linker that act as a hinge point and assumed that a Pro461Gly and a Gly460+ (with an extra glycine) constructs of a Cel9A-68 would present enhanced interdomain motions, while the Gly460Pro mutant would be rigid. The Pro461Gly mutation resulted in an extension of the conformational space, as confirmed by clustering and free energy analyses.…”
Section: Modify the Enzymes And Increase Their Efficiencymentioning
confidence: 99%